2002
DOI: 10.1177/154193120204601904
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Warnings Design: Do They Matter?

Abstract: A study was carried out using four measures of effectiveness to compare product warnings that are consistent with the American National Standards Institute Product Safety Signs and Labels standard (ANSI 2535.4) to warnings that are not consistent with the standard. Inconsistent warnings were based on the format of existing product warnings. Two warnings, consistent and inconsistent, for each of ten different products were evaluated: cooking oil, trampoline, paint, dresser, airbag, seat belt, tire, sports uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 6 publications
5
25
0
Order By: Relevance
“…Further, only 28 percent of respondents said they made a practice of frequent adjustment of the head restraints. Laughery, Paige, Laughery, Wogalter, Kalsher, and Leonard (2002), using respondents from five different states, found that warnings designed to conform to the ANSI Z535.4 standard (1998) were rated about 1.5 to 2 times as effective as warnings that did not follow that format. As seen in Table 1, similar results were obtained from these participants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, only 28 percent of respondents said they made a practice of frequent adjustment of the head restraints. Laughery, Paige, Laughery, Wogalter, Kalsher, and Leonard (2002), using respondents from five different states, found that warnings designed to conform to the ANSI Z535.4 standard (1998) were rated about 1.5 to 2 times as effective as warnings that did not follow that format. As seen in Table 1, similar results were obtained from these participants.…”
Section: Resultsmentioning
confidence: 99%
“…The question of what warnings to provide and how to present them is not always easy to answer. Previous research (Laughery et al, 2002) has shown that using warnings designed on principles accepted in the human factors/ergonomics approach to warnings is thought to increase the likelihood that they will be noticed and obeyed. Further, evidence has been shown to support the notion that more information about hazards increases the subjective concern for avoiding the hazards (Leonard, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, there has been a persistent treatment of warning labels and signs as components, and the development of the ANSI Z535 standards for labels, signs, tags, and instructions along with their colors and symbols reflects a tendency for HF professionals to reify warnings. It is an indication of progress that the ANSI safety information standards are increasingly tied to empirical research; it is also encouraging to note the open debate about the utility of these standards (e.g., Laughery et al, 2002;Frantz et al, 2005) Warnings research in the HF[E]S has evolved over time. Some of the first papers presented on warnings raised a challenge by pointing out a lack of empirical research on compliance with warnings (Dorris & Purswell, 1978;McCarthy et al, 1984).…”
Section: Research Historymentioning
confidence: 99%
“…Research with adults reveals a number of factors that affect viewers’ understanding of the message communicated by a warning sign, include the language expressed (e.g., word choice, explicitness) and pictorial images shown. Including a signal word (e.g., Caution , Warning , Danger ) that is immediately understood as communicating something about risk is an essential feature on warning signs [ 16 ]. The explicitness of the messaging also affects understanding.…”
Section: Introductionmentioning
confidence: 99%